2009
DOI: 10.1186/1471-2458-9-9
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of chronic diseases and major disease risk factors at different ages among 150 000 men and women living in Mexico City: cross-sectional analyses of a prospective study

Abstract: Background: While most of the global burden from chronic diseases, and especially vascular diseases, is now borne by low and middle-income countries, few large-scale epidemiological studies of chronic diseases in such countries have been performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
72
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 6 publications
5
72
0
2
Order By: Relevance
“…comparative tasks in the same format) also seem to be most effective at drawing attention to itself, an early stage of information processing. In short, the label that we find to garner the most attention, a color-coded FOP, is also the label that researchers who have focused on the late stages of cognitive processing (comprehension) have also found to be easiest to comprehend and use 26, 3135 . The combination of our results with those on comprehension suggests that color coded FOPs are more effectively processed at multiple stages of information processing (see Table 1), and thus is likely to be a more effective method of nutrition labeling.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…comparative tasks in the same format) also seem to be most effective at drawing attention to itself, an early stage of information processing. In short, the label that we find to garner the most attention, a color-coded FOP, is also the label that researchers who have focused on the late stages of cognitive processing (comprehension) have also found to be easiest to comprehend and use 26, 3135 . The combination of our results with those on comprehension suggests that color coded FOPs are more effectively processed at multiple stages of information processing (see Table 1), and thus is likely to be a more effective method of nutrition labeling.…”
Section: Discussionmentioning
confidence: 66%
“…Researchers from the UK 71 , concluded that color-coded FOPs (traffic lighting) significantly enhanced participants’ abilities to arrive at a judgement regarding product “healthfulness.” This finding was echoed by a study conducted in Germany in which a color-coded FOP enhanced the chances of making a correct evaluation of the healthier choice of product during a binary force choice task compared to other types of nutrition labels. 26 Likewise, Australian researchers concluded that people were five times more likely to correctly identify a food as healthy when labeled with a traffic light FOP than a monochromatic FOP scheme. 32 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations